EFEKTIVITAS EKSTRAK DAUN SALAM (Syzygium polyanthum) SEBAGAI ANTIDIARE PADA MENCIT BALB/C (Mus musculus) - Khafidloh, Muizzatul; Sulistiawati, Erni; Sagatana, Ervina Nanda (LPPM Sekolah Tinggi Ilmu Farmasi Nusaputera, 2025)
Bay leaves as a cooking ingredient in Indonesia are also a herbal medicinal plant as a traditional treatment for digestive problems such as diarrhea. This research aims to obtain information on the effective dosage of bay leaf extract (Syzygium polyanthum) as an antidiarrhea. This research used 15 mice and divided them into 5 groups which were carried out using two methods, namely intestinal protection and intestinal transit. The requirements are divided into negative control (1% CMC-Na suspension), positive control (Loperamide HCl 0.26 mg/KgBW), and groups with graded doses (50 mg/KgBW, 100 mg/KgBW, and 150 mg/KgBW) given sequential orally. The parameters observed in this study were defecation frequency, stool consistency, and the ratio of marker passages in the intestines of mice. A dose of 150 mg/KgBW provides the best antidiarrheal effect. This is proven by the significantly different results in the two methods that have been carried out for the drug loperamide. The content of tannins, flavonoids, and alkaloids in bay leaves provides an antidiarrheal effect on diarrheal diseases.